Adaptive Agripreneurship: How CSR Partnerships Empower Disabled Farmers for Economic Independence - Nurhayati, Sri; Munggarani, Febi; Boriboon, Gumpanat; Jacob, Udeme Samuel; Lotfi, Fatima Zahra (Prosperity: Journal of Society and Empowerment, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) partnerships on empowering disabled farmers within the "Tumbuh Mandiri Cimahi" (TUMAN) Disabled Farmers Group in Indonesia. It tackles the key challenges faced by marginalized communities, including limited resources, inadequate skills, and restricted market access. Using a qualitative case study approach, data were gathered through in-depth interviews, non-participatory observation, and document analysis involving TUMAN members and relevant stakeholders. Thematic analysis indicated that CSR engagement significantly enhances participants’ agricultural skills, income security, and sense of social inclusion. The program provides customized training, adaptive farming tools, and market connections, enabling participants to attain greater economic independence. Moreover, TUMAN prioritizes local partnerships and ongoing capacity-building, which supports long-term sustainability. The findings illustrate that CSR can serve as a transformative force in disability-inclusive agripreneurship, promoting both social equity and economic resilience in rural areas. This research contributes to the discourse on inclusive community development by presenting a replicable model that integrates CSR with empowerment-focused strategies. The study offers practical insights for policymakers, development practitioners, and CSR stakeholders dedicated to advancing inclusive and sustainable rural livelihoods.